Changes in lake sturgeon spawning periodicity is associated with prior reproductive effort - Douglas L. Larson; Travis O. Brenden; Edward A. Baker; Kim T. Scribner (Scientific Reports)
Abstract Long-lived iteroparous organisms vary resource expenditures toward migration and reproduction in response to individual physical factors and conspecific interactions, which can affect future reproductive timing and interval. Reproductive actions can lead to trade-offs associated with allocations to current vs. future reproduction, including longer reproductive interval, require additional study. The objective of this study was to evaluate associations between physical stream characteristics, individual behaviors, and breeding demographics and spawning periodicity in lake sturgeon (Acipenser fulvescens). We used Radio Frequency Identification tags to monitor spawning migration by male (N = 1931) and female (N = 683) adults over seven consecutive years (2016 through 2022) in the Black River, Cheboygan Co., MI. We used ordinal regression models to quantify associations. Male spawning periodicity (1.60 ± 0.63 years; mean ± SE) decreased with increasing body size and intra-sex interactions and increased with increasing cumulative temperature, discharge, number of inter-sex interactions, and complete river migrations in a season. Female spawning periodicity (3.19 ± 0.05 years, mean ± SE) decreased with increasing upstream swimming time and inter-sex interactions. Results demonstrated spawning periodicity shortened as male lake sturgeon age, and future breeding opportunities decreased, while female periodicity may be more individualized and is more likely to be affected by resource acquisition.